Influence of Apolipoprotein E polymorphism on susceptibility of Wilson disease. (23rd October 2017) - Roy, Shubhrajit; Ganguly, Kausik; Pal, Prosenjit; Ghosh, Sampurna; Das, Shyamal K; Gangopadhyay, Prasanta K.; Bavdekar, Ashish; Ray, Kunal; Sengupta, Mainak; Ray, Jharna
Abstract: Wilson disease (WD) is an autosomal‐recessive disorder caused by mutations in the ATP7B gene leading to abnormal copper deposition in liver and brain. WD manifests diverse neurological and hepatic phenotypes and different age of onset, even among the siblings, with same mutational background suggesting complex nature of the disease and involvement of other candidate genes. In that context, Apolipoprotein E (APOE) and Prion Protein ( PRNP ) have been proposed to be potential candidates for modifying the WD phenotype and age of onset. This study aims to identify the contribution of APOE and PRNP polymorphisms on the variable phenotypic expression of Indian WD patients. A total of 171 WD patients and 291 controls from Indian population were included in this study. Two APOE cSNPs (rs429358 and rs7412) resulting in three isoforms and M129V (rs1799990) polymorphism of PRNP were examined for their association with WD and its clinical phenotypes. The APOE ԑ4 allele was found to be significantly overrepresented in WD patients compared to controls. However, the frequency of the APOE ԑ3 allele and ԑ3/ԑ3 genotype was significantly higher in WD patients without cognitive behavior impairment compared to the ones with the impairment. On the contrary, the PRNP allele representing Val129 was found to be present in higher proportion in WD patients with cognitive behavioral decline. Our data suggest that the APOE ԑ4 allele could act as a potential risk for the pathogenesis of WD. Also, APOE and PRNP might contribute toward the cognitive behavioral decline in a section of WD patients.